Relationship of dyslipidemia and autovenous femoro-popliteal bypass outcome - А. S. Artemova; M. A. Сhernyavsky (Атеросклероз, 2022)
The effect of blood lipid profile levels on the service life of autovenous femoral-popliteal bypass has not been fully studied. The aim of the study was to assess the effect of lipid metabolism disorders on the long-term results of autovenous femoral-popliteal bypass surgery. Material and methods. Results of treatment of 648 patients who underwent autovenous femoral-popliteal bypass grafting were analyzed. In accordance with the outcome of surgical treatment, the patients were divided into 2 clinical groups: the first group (290 patients) included patients who, according to the instrumental methods of research in the long-term period, had occlusion of the autovenous femoral-popliteal bypass, the second group (358 people) included patients whose autovenous conduit was passable. The average service life of the autovenous femoral-popliteal bypass in patients of the first group was 78 ± 18 months. Patients in the first and second groups aged 64.5 ± 7.9 and 64.9 ± 8.6 years, respectively, p = 0.58, males prevailed (n = 503, 77.62 %). Results. Analysis of lipidogram data showed higher content of total cholesterol, low density lipoprotein, triacylglycerol, atherogenic coefficient in patients of the first clinical group. Dyslipidemia was recorded in 256 (88.3 %) patients of the first group and 190 patients of the second group (53.1 %), p = 0.001. The patency time of the autovenous conduit in patients of the first group, who was diagnosed with dyslipidemia, was 68.15 months, without this complication – 105.84 months. Conclusions. Dyslipidemia and hyperlipidemia significantly reduce the lifespan of the autovenous femoral-popliteal bypass. The work has no funding